The Potential of Palm Oil Waste Biomass as a Mushroom Growing Medium: A Preliminary Study of Nutrient Content - Julsento HP; Herlina Mega Puspitasari; Wini Prayogi Abdila (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The expansion of oil palm plantations has resulted in large amounts of biomass waste that has the potential to be used as a substrate for mushroom cultivation. However, information on the nutrient content of various types of oil palm waste is still limited. This study aims to analyze the macro nutrient content (organic C, N, P, K, Ca, Mg) and C/N ratio of three types of palm oil waste, namely empty fruit bunches, fronds, and leaves. Laboratory analysis was performed using the Walkley Black method for organic C, Kjeldahl for total N, and Atomic Absorption Spectroscopy (AAS) for P, K, Ca, and Mg. The results showed that empty fruit bunches had the highest organic C content (57.24%) and relatively high K and Mg, making them a potential carbon source. Leaves have a higher N content (0.26%) with the lowest C/N ratio (114.58), making them decompose more quickly. Fronds have the highest Ca content (0.61%) but a very high C/N ratio (332.40), requiring a longer decomposition time. Overall, each type of palm oil waste has specific nutrient advantages that can complement each other when used in combination. These results provide a scientific basis for utilizing palm oil waste as a more efficient and environmentally friendly alternative growing medium in mushroom cultivation.